Thermoneutral design aspects of gasoline chemical looping reformer - Kale, G. R.; Kulkarni, B. D. (Fuel Cells, 2013)
Chemical looping reforming (CLR) is a new technology for syngas generation. The theoretical process design aspects of syngas generation using CLR of isooctane (gasoline) are studied in this paper to assess its ability for fuel processor development for solid oxide fuel cells. The fuel processor operating conditions for maximum syngas generation at thermoneutral conditions are determined in this study using nickel oxide as oxygen carrier for different inputs of oxygen carrier within the temperature range of 600-1,000 degrees C at 1bar pressure. The thermoneutral temperatures for the dual reactor fuel processor were calculated using the hot product gas stream and exothermic CLR process enthalpy to completely balance the endothermic process requirements. The thermoneutral point of 879.5 degrees C (NiO input of 7moles) delivered maximum syngas (13.92moles) using lowest amount of air (26.13moles) in the process was found to be the most suitable thermoneutral temperature for the fuel processor operation. The novel fuel processor design can also be used for other fuels and oxygen carriers.
Keywords: Chemical Looping Reformer; Fuel Processor; Isooctane to Syngas; Oxygen Carrier; Thermoneutral Temperature